A Tune in “A Minor” Can “B Major”: A Review of Epidemiology, Illness Course, and Public Health Implications of Subthreshold Depression in Older Adults - Meeks, Thomas (2011)
BACKGROUND: With emphasis on dimensional aspects of psychopathology in development of the upcoming DSM-V, we systematically review data on epidemiology, illness course, risk factors for, and consequences of late-life depressive syndromes not meeting DSM-IV-TR criteria for major depression or dysthymia. We termed these syndromes subthreshold depression, including minor depression and subsyndromal depression. METHODS: We searched PubMed (1980–Jan 2010) using the terms: subsyndromal depression, subthreshold depression, and minor depression in combination with elderly, geriatric, older adult, and late-life. Data were extracted from 181 studies of late-life subthreshold depression. RESULTS: In older adults subthreshold depression was generally at least 2–3 times more prevalent (median community point prevalence 9.8%) than major depression. Prevalence of subthreshold depression was lower in community settings versus primary care and highest in long-term care settings. Approximately 8–10% of older persons with subthreshold depression developed major depression per year. The course of late-life subthreshold depression was more favorable than that of late-life major depression, but far from benign, with a median remission rate to non-depressed status of only 27% after ≥1 year. Prominent risk factors included female gender, medical burden, disability, and low social support; consequences included increased disability, greater healthcare utilization, and increased suicidal ideation. LIMITATIONS: Heterogeneity of the data, especially related to definitions of subthreshold depression limit our ability to conduct meta-analysis. CONCLUSIONS: The high prevalence and associated adverse health outcomes of late-life subthreshold depression indicate the major public health significance of this condition and suggest a need for further research on its neurobiology and treatment. Such efforts could potentially lead to prevention of considerable morbidity for the growing number of older adults.